2017
DOI: 10.1007/s11743-017-2002-4
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Surface Activity of Cationic Amino Acid‐Based Surfactants in Aqueous Solution

Abstract: I studied the possibility of using amino acid-based surfactants as emulsifiers at the same time as preservatives. Fourteen lipopeptides were synthesized employing a solid phase peptide synthesis procedure. All compounds were designed to be positively charged from +1 to +4 and acylated with fatty acid chain—palmitic and miristic. The surface activity of the obtained lipopeptides was tested using a semi-automatic tensiometer to calculate parameters describing the behavior of lipopeptides in the air/water interfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…As expected, the critical aggregation concentration ( CAC ) values increased in the homologue series, i.e., Lys, Orn, Dab, and Dap, with a linear relationship of log CAC vs. number of methylene groups in the side chain of palmitoylated residue ( Figure S3, Supplementary Materials ). A comparison of the result obtained for K(K C16 )K-NH 2 with that for C 16 -KKK-NH 2 [ 22 ] showed that the transfer of the palmitoyl chain from the N -terminus of the peptide chain to the ε- N -amine group of the central lysine increased the CAC from 4.8 to 5.4 mM. The modification of the acyl chain position separated the positive charge centers located on the lysine side chains, changed mutual arrangement of the headgroups relative to the hydrocarbon tails, and increased the cross-sectional area of the polar heads.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As expected, the critical aggregation concentration ( CAC ) values increased in the homologue series, i.e., Lys, Orn, Dab, and Dap, with a linear relationship of log CAC vs. number of methylene groups in the side chain of palmitoylated residue ( Figure S3, Supplementary Materials ). A comparison of the result obtained for K(K C16 )K-NH 2 with that for C 16 -KKK-NH 2 [ 22 ] showed that the transfer of the palmitoyl chain from the N -terminus of the peptide chain to the ε- N -amine group of the central lysine increased the CAC from 4.8 to 5.4 mM. The modification of the acyl chain position separated the positive charge centers located on the lysine side chains, changed mutual arrangement of the headgroups relative to the hydrocarbon tails, and increased the cross-sectional area of the polar heads.…”
Section: Resultsmentioning
confidence: 99%
“…We speculate that due to large steric hindrance of the hydrophilic groups, the KK(X C16 )KK-NH 2 peptides undergo self-assembly at a concentration several times higher than that for K(X C16 )K-NH 2 counterparts. Our assumption is based on a study on the N -terminally palmitoylated lysine-based peptides [ 22 ]. The linear dependence of log CAC on the number of lysine residues ( Figure S3, Supplementary Materials ) allowed us to roughly estimate a CAC value for C 16 -KKKKK-NH 2 to be around 60 mM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their mode of action is based on the permeabilization of the membrane bilayers, what leads to cell death [13][14][15]18 . They can exhibit plenty of biological properties, such as antibacterial, antifungal, antibio lm, antiadhesive, anticancer and surface activities 19 . On the other hand, USCLs can be noticeably lytic to erythrocytes and cytotoxic to normal human cells 13,15,18 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the aim of the present study was to evaluate a holistic approach combining a low temperature, antibiotic-free storing procedure for boar sperm with the use of alternative antimicrobial agents. The applied substances were a group of seven short lipopeptides derived from the two amino acid derivatives Fmoc-Lys(Boc)-OH and Fmoc-Lys(Fmoc)-OH 16 , 17 . Short lipopeptides possess many of the qualities of the more in-depth studied AMPs stated above (amphipathic, positively charged, antimicrobially active) while being less cost- and time-consuming in production 18 .…”
Section: Introductionmentioning
confidence: 99%